2022
DOI: 10.1136/bmjgh-2022-008909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of home-based childcare on childhood mortality in rural Maharashtra, India: a cluster randomised controlled trial

Abstract: BackgroundMelghat, an impoverished rural area in Maharashtra state, India; has scarce hospital services and low health-seeking behaviour. At baseline (2004) the under-five mortality rate (U5MR) (number of deaths in children aged 0–5 years/1000 live births) was 147.21 and infant mortality rate (IMR) (number of deaths of infants aged under 1 year/1000 live births) was 106.6 per 1000 live births. We aimed at reducing mortality rates through home-based child care (HBCC) using village health workers (VHWs).MethodsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Figure 2 shows that prevalence of VAD induced ocular morbidity in the present study is 2.75 per cent, which is of moderate public health problem as per the WHO 25 . This is much higher than the prevalence in India (<1%) 13 and the world (in the age group of 5-19 yr <0.1%) 26 . In the adolescent tribal population of India, VAD prevalence was bitot’s spots (2%) and conjunctival xerosis (4.9%).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Figure 2 shows that prevalence of VAD induced ocular morbidity in the present study is 2.75 per cent, which is of moderate public health problem as per the WHO 25 . This is much higher than the prevalence in India (<1%) 13 and the world (in the age group of 5-19 yr <0.1%) 26 . In the adolescent tribal population of India, VAD prevalence was bitot’s spots (2%) and conjunctival xerosis (4.9%).…”
Section: Discussionmentioning
confidence: 64%
“…A systematic review of 30 community-based studies in India revealed that the prevalence of visual impairment was 2.05 to 13.6 per thousand and that of childhood blindness was 0.6 to 1.06 per thousand, respectively 13 . In north India, preventable and/or treatable conditions contributed to 50 per cent of the blind school children 14 .…”
mentioning
confidence: 99%
“…The population is 300,000 with 84 per cent poor tribal, 50 per cent semiliterate/illiterate, mostly small farmers/labourers. Melghat has poor transportation, grossly inadequate health services and low health seeking behaviour, leading to high mortality 11 .…”
Section: Methodsmentioning
confidence: 99%
“…It was reviewed by the principal investigator. Multiple methods were used for death data collection in the community to improve the accuracy of death statistics 11 .…”
Section: Methodsmentioning
confidence: 99%
“…In a large RCT involving 34 villages in a poor rural area in Maharashtra state, India, village health volunteers that engaged in newborn care, disease management and behaviour change communications resulted in large and sustained reductions in infant and child mortality 31…”
mentioning
confidence: 99%